Pengaruh Efikasi Diri Terhadap Intensi Berwirausaha Mahasiswa Pendidikan Ekonomi Dengan Kreativitas Sebagai Variabel Mediator - Fatma Arianti Hasanah; Mohamad Arief Rafsanjani (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
The level of student participation in the field of entrepreneurship is very low, namely 1.2 percent, student participation in entrepreneurship should not be below 2 percent. Therefore it is very important in increasing entrepreneurial intentions in students. This study aims to determine the effect of self-efficacy on the entrepreneurial intentions of UNESA students in the 2019 class of economic education study program with creativity as a mediator variable. This type of research is explanatory research. The sample that will be used is 48 students while the sampling technique is purposive sampling technique. For data analysis techniques using path analysis and sobel test. In the results of the statistical test above, it can be seen that the Z value is 2.99 1.96 where it can be concluded that the results of the data analysis are creativity is able to mediate the relationship between Self-Efficacy and Entrepreneurial Intentions of UNESA Students in Economic Education Study Program, Class of 2019 or there is an indirect influence between Self-Efficacy and Entrepreneurial Intention because of the creativity variable